Level of Acceptance of Filipino Facebook Users on the Contrivance of Ludic Language - Bansolay, Caren Rimando (IJRDO- Journal of Educational Research, 2018)
This study identified the level of acceptance of Filipino facebook users on the contrivance of ludic language. Furthermore, this study aimed to determine if there are differences on their level of acceptance when grouped according to age, gender and nature of work. Based on the findings, facebook users generally favor the contrivance of ludic language not so strongly. Results also unfold that there are differences in the level of their acceptance that ages 11-14 favor strongly, ages 15-19 favor not so strongly, ages 20-35 oppose strongly, and ages 36 and above oppose not so strongly; male favor not so strongly and female oppose strongly; and, facebook users whose job is related to arts favor strongly, those in education oppose strongly, those in management favor not so strongly, those in science fields oppose not so strongly, and students favor strongly. These findings are seen to have pedagogical significance for ESL or EFL teachers; language play may provide insight into learners’ diverse competencies, may encourage frolic output, and may be a viable tool for encouraging language learning. The researcher further recommends the need of research on language play to assess its efficacy as a pedagogical technique and to determine its implications in the field of second language learning. Further research on the use of social networking sites as a medium of communication may be conducted to assess the depth of media literacy among the identified respondents, for the need of literacy in using media for any purpose is, at this time, fundamental.